ANALISIS KESULITAN BELAJAR MATERI STATISTIKA PADA MAHASISWA PGSD KELAS 1C - Cyntia Paramita; Donada Cecilia Avondy; Yuny; Rian Damariswara (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Learning difficulties are a common problem faced by students, which can affect the quality of education and learning outcomes. This study aims to analyze the factors that affect learning difficulties in students and develop prevention strategies to overcome these problems. The results showed that factors such as academic ability, motivation, and learning environment had a significant effect on learning difficulties. Based on these results, preventive strategies such as developing academic ability, increasing motivation, and improving the quality of the learning environment are recommended. This research is expected to contribute to the development of strategies to prevent learning difficulties in students and improve the quality of Education. Keywords: student, difficulty, statistical material